Highlights and Main Findings from the 8 Year SOLVit R&D Programme – Bringing Solvents and Technology from Laboratory to Industry. (July 2017) - Knudsen, Jacob N.; Wærnes, Ole; Svendsen, Hallvard F.; Graff, Oscar
Abstract: SOLVit is an eight year (2008 – 2015) and 37 million Euro research programme focusing on developing energy efficient and environmental friendly post combustion carbon capture systems for large-scale industrial CO2 emissions. The programme is coordinated by Aker Solutions. Work has been conducted within the fields of solvent development, process optimisation and operational understanding through pilot plant testing. Several new solvents have been developed in the project offering up to 35% improvement in energy consumption relative to MEA along with significantly improved degradation and environmental performances. SOLVit has improved the maturity of Aker Solutions' Advanced Carbon Capture TM process significantly.